Antibiotics susceptibility pattern and prevalence of isolated uropathogens in inpatient and out patients with lower urinary tract infections - Ranakishor Pelluri, Paditham Monika, Harika Paritala, Chandrika Reddy Annapareddy, Bhuvaneswari Kotha, Srujana Meenavilli, Sandhya Rani Angadi, Geethika Rayapati, Srinivasababu Puttagunta (Journal of Applied Pharmaceutical Science, 2021)
Bacterial resistance was the consequence of empirical therapy and poor compliance, and its amelioration was difficult. In both in-patients and out-patients, definitive therapy resulted in better outcomes for urinary tract infections (UTI). Our objective was to identify the prevalence and to assess the susceptibility pattern of uropathogens toward antibiotics. It is a prospective, cross-sectional study conducted during the period of November, 01, 2019 to April, 28, 2020. A total of 200 UTI patient’s antibiotic susceptibility pattern was analyzed of which, 105 were males and 95 were females. Among them, 147 were in-patients and 53 were out-patients. The prevalence of UTI was high between the ages of 40 and 79 years. Less than 20% susceptibility was noticed in 20–39 years of age groups and less than 10% were observed in 80–99 years of age groups. The antibiotic susceptibility was found to be 35%–40% among the 40–59 years of age group, of them Ertapenem and Trimethoprime (TMP) & Sulfamethoxazole (SMZ) only has 48.5% and 44.6% of susceptibility and literally poor in 80–99 years. Colistin and Amikacin showed higher susceptibility toward Escherichia coli and Klebsiella pneumoniae in in-patients. The remaining antibiotics showed 40%–67% of susceptibility. TMP and SMZ, Amoxicillin Clavulanic acid, Cefoperazone, and Amoxicillin plus Clavulanic acid had relatively low susceptibility (16%–27%). Colistin, Amikacin, and Nitrofurantoin showed better susceptibility in in-patients and in out-patients. TMP and SMZ, Amoxicillin Clavulanic acid, Cefoperazone, and Amoxicillin plus Clavulanic acid had relatively low susceptibility. Escherichia coli was more prevalent Gram-negative bacteria isolated among the individuals and 57.8% of In-patients (IP) and 67.9% of out-patients (OP) with UTI were isolated with E. coli.
Keywords: Lower UTI, uropathogens, antibiotic susceptibility, in and out patients, South India